Introduction to Hospitality Operations / An Indispensable Guide to the Industry: Second Edition - Jones Peter (Continuum, 2002)
This book examines the whole of the hospitality industry and the ways in which it operates. Preface, The Hospitality Industry, The Accommodation Industry, The Accommodation Sector, Business and Conference Hotels, Resort Hotels, Budget Hotels, Guest Houses and Small Hotels, Hospital Hotel Services and Residential Care, Hostels and Halls of Residence, The Foodservice Industry, The Foodservice Sector, Restaurants, Foodservice Operations in Hotels, Motorway and Roadside Dining, Licensed Trade Foodservice, Fast Food, Employee Feeding, Welfare Catering, Travel Catering, Outside Catering, References, Index.